Debate Over Law Number 17 of 2023 Concerning Community Organizations: Maqasid Al-Shari’ah Review - Sanuri, Sanuri (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
This study explores the debate over Law Number 17 of 2013 concerning Community Organizations (COs) in light of the Maqasid al-Shari'ah Framework (MSF). MSF is a theoretical construct used in Islamic law to identify the higher objectives and purposes of the legal system. Using a qualitative approach, this study examines the perspectives of key stakeholders, including government officials, legal experts, and civil society organizations, on the law's compatibility with the objectives of the Islamic legal system. The findings of this study are: first, for the contexts of Indonesia, Law Number 17 of 2013 should further protect to five essential aspects of human life, namely religion, soul, mind, lineage, and property; second, based on the feature of qat'i al-dalalah (certainty in Islamic law), what the Government did by restricting and providing conditions to COs is the form of the government's responsibility to protect the State from various efforts that could threaten the Unitary State of the Republic of Indonesia; third, the COs’ various visions and missions that are increasingly far from the values of Pancasila and the 1945 Constitution reinforce the potential for disintegration of the nation is classified as daruriyyah (emergency) in nature that is in need of a strict policy from the Government; and fourth, dissolution of the COs, as stipulated in Law Number 17 of 2013, is as a reflection of implementing more prioritizing maqasid al-'ammah (universal goals) than maqasid al-khassah (specific goals).